The Development of the Himasindo Theater, Faculty of Teacher Training and Education, Lambung Mangkurat University, 1995-2020 - Muhammad Raihan Budiman; Mansyur, Mansyur; Bambang Subiyakto (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The journey of theater in Indonesia demonstrates a long and dynamic historical process over time. In Banjarmasin, the development of theater arts contributed significantly to the emergence of theater communities within universities, both public and private, through student activity units. Himasindo Theater, under the Faculty of Teacher Training and Education, Lambung Mangkurat University, Banjarmasin, was officially established in 1995. This study aims to describe and analyze the development of the Himasindo Theater, Faculty of Teacher Training and Education, ULM, from 1995 to 2020. The research employed historical methods encompassing four main stages: heuristics, criticism, interpretation, and historiography. The results show that Himasindo Theater experienced ups and downs in its organizational aspects, from lacking a clear organizational structure to becoming a more focused organization. However, its status as a faculty-level Student Activity Unit (UKM) limited its membership, resulting in a decline in membership and decreased productivity. In its creative field, Teater Himasindo displays its distinctive characteristics through experimental, surrealist, and realist styles, influenced by different thinkers from different eras.